Genetics of flag leaf angle, width, Length and area in bread wheat (Triticum aestivum) - Singh, G P; Chaudhry, H B; Yadav, Rajbir (The Indian Journal of Agricultural Sciences, 2008)
The study was conducted for winter (rabi) seasons of 2005-06 and 2006-07 at New Delhi in wheat (Triticum aestivum L. emend. Fiori & Paol.), to study the genetic architecture of some bread wheat cultivars for grain yield and flag leaf related traits and selection of promising genotypes for incorporation of desirable traits using 6x6 diallel involving 6 bread wheat lines ’PBW 343’, ’NW 1012’, ’NW 2036’, ’RAJ 3765’, ’HD 2285’ and ’DBW 14’ making crosses in all possible combinations without reciprocals. The results indicated that additive variance component (D) was significant for flag leaf width and flag leaf area. The dominance variance components (H1) was significant for the characters flag leaf width, flag leaf angle and grain yield, whereas the dominance level variance component (h2) and the corrected dominance component (H2) were significant for all the characters flag leaf length, flag leaf width, flag leaf area, flag leaf angle and grain yield. Flag leaf length was positively and significantly correlated with flag leaf width (r2= 0.693), flag leaf area (r2= 0.732) and flag leaf angle (r2= 0.367). The flag leaf width was positively and significantly correlated with flag leaf area (r2= 0.467), whereas the flag leaf area and flag leaf angle were positively and significantly correlated with grain yield (r2= 0.660,0.468 respectively).